Analisis produksi tanaman pangan nasional: statistik deskriptif dan tren bulanan produksi padi dan jagung tahun 2025 - Salsabila, Dani Dwi (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the production of national food crops, particularly rice and maize, using descriptive statistics and monthly trend analysis. The data were obtained from the Central Bureau of Statistics (BPS) for the period of January to July 2025. The results indicate that rice production experienced significant fluctuations, with a sharp increase from January, peaking in March–April, and then declining from May to July. In contrast, maize production showed a more stable pattern; although there was an increase in February and a slight decrease in May, the overall trend remained relatively consistent from month to month. The descriptive analysis highlights a clear difference in seasonal characteristics between the two commodities. Rice production is strongly influenced by planting seasons and harvest cycles, while maize tends to have a more evenly distributed production throughout the year. These findings suggest that the fluctuations in rice production and the stability of maize production can complement each other in maintaining food availability. Therefore, this study provides a useful basis for further research on the dynamics of food production and its role in supporting national food security.